NEW TECHNOLOGIES IN CONSTRUCTION - Assemgul Yerzhanova (Research Retrieval and Academic Letters, 2023)
Investment in ConTech has skyrocketed in recent years, reaching unprecedented demand. The industry is making efforts to innovate, streamline and digitalize as it increases its resilience. Building technology funding hit a record $5.38 billion in 2022, down 1% from $5.4 billion in 2021, according to CEMEX. The industry has shown strong performance compared to other sectors and venture capital in general (1). Investment by region increased in North America and the EU: they account for the "lion's" share in the world. However, the Asia-Pacific region and the Middle East are showing significant growth. A commitment to investing in building technology has been a long-term strategy for decades, as evidenced by the wide range of deals made in 2022. Contech's top 50 startups include businesses focused on green building, construction supply chain, productivity improvement, and the future of construction. And this investment in innovation is paying off. Research shows that companies that adopt technology increase their bottom line by 48% in revenue and 15% in net margin. The technology market continues to change at an accelerated pace, innovation will lead to even greater development and progress. Already, there are more than a dozen demanded technologies. The main trends in the second half of 2023 are similar to previous years. But the market makes its own adjustments, because for the conservative construction market, all these are experimental techniques. And so far, the participants are only adapting to them, developing a format in which these techniques will take root, and then standardization, development of standards, and so on will be required. Technologies will be selected and evaluated empirically to identify leaders and apply the most practical solutions. Analysts are now betting on cloud computing, project management software, the ubiquity of drones and sensors, house printing technology, and of course BIM technologies in construction, which allow creating digital twins and using virtual and augmented reality tools to deeply understand the project. But some technologies, although already on everyone's lips, still have not found widespread use. For example, despite the global relevance of building information modeling (BIM), its complexity and high cost limit its use in digitalization. Instead, mobile construction apps are becoming more popular. They give results in real time and have practical value already at the current stage, without the need for long-term implementation.